The prince's body: Vincenzo Gonzaga and Renaissance medicine - Finucci, Valeria (I Tatti studies in Italian Renaissance history, 2015)
"This book is part of the current debate among historians of medicine, cultural studies theorists, gender and sexuality scholars, and literary critics regarding key interrelated preoccupations of the early modern period (or indeed of any period): sexuality, reproduction, beauty, and aging. The author uses as her guide four notorious moments in the life of Duke Vincenzo Gonzaga of Mantua (1562-1612), a well-known patron of arts and music in Renaissance Italy. By examining documents in the Gonzaga and Medici archives--letters, doctors' advice, reports, receipts, travelogues--together with (and against) medical, herbal, theological, even legal publications of the period, she fleshes out an early modern cultural history of the pathology of human reproduction, the physiology of aging, and the science of rejuvenation as they impacted a prince with a large ego and an even larger purse. The questions addressed are wide-ranging: How did the discovery of new body parts translate into political empowerment? What specific physiological issues impacted couples' reproductive agendas? When did the worshipping of beauty motivate radical experimentations with aesthetic surgery?"--Provided by publisher